GW26-e2286 MRI tissue perfusion evaluation in patients with chronic limb ischemia compared with healthy subjects - Sinkevich, Nadezda; Butorova, E.; Maslennikov, M.; Stukalova, O.; Bulkina, O.; Ternovoy, S.; Karpov, Yu (Journal of the American College of Cardiology, 2015)
All performed supine plantar flexion exercise in a 1.5T MRI scanner for 5 minutes or until limiting symptoms with intravenous gadolinium-based contrast media administration (GdDPA).